COST VALUE-STREAM MAPPING AS A LEAN ASSESSMENT TOOL IN A SURGICAL GLOVE MANUFACTURING COMPANY - Menon, Rajesh B; Shalij, P R; Sajeesh, P; Tom, Geemon; Pramod, V R (The South African Journal of Industrial Engineering, 2021)
The development of cost-integrated value-stream mapping (CVSM) as a lean assessment tool for identifying wastage in the production process is presented in this article. In conventional VSM, the time involved in various processes is mapped without tracking the accumulation of direct and indirect costs. In the proposed CVSM, the cost of production is also accounted for, along with the time domain of conventional value-stream mapping. The time investment of the cost is also incorporated in CVSM. Value-added and non-value-added costs can thus be easily recognised in the time scale This novel method helps to calculate the value addition in monetary terms, and thus the actual production cost of the processes is acknowledged accurately. Since the wastage is quantified in the cost domain, the processes in which lean tools need to be implemented can be identified. The details of establishing CVSM are presented along with a study of its implementation in a glove manufacturing industry.